Occurrence and natural history of Myrmelachista Roger (Formicidae: Formicinae) in the Atlantic Forest of southeastern Brazil - Nakano, Márcia Akemi; Miranda, Vitor F. Oliveira de [UNESP]; Souza, Débora Rodrigues de; Feitosa, Rodrigo M.; Morini, M. Santina C. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2013)
Information on the biology of the species in Myrmelachista remains notably scarce. The objective of this study was to report the occurrence, analyze the influence of canopy cover on the number of nests in twigs in the litter describe behavioral characteristics of this genus. Hand sampling was performed on trees and twigs deposited in the litter. A total of 84 nests and seven species were found. Myrmelachista ruszkii and M. catharinae were the most frequent and abundant species. In trees, most of the nests were located at the ti ps of dry twigs, and these nests were probably the source of the nests found in the litter of fragments of Atlantic Forest of southeastern Brazil. Canopy cover is associated with the number of nests that were in twigs. © Sociedad de Biología de Chile.
Keywords: Canopy; Dense ombrophilous forest; Polydomy; Reproduction; Tree species